VARIABILITAS KANDUNGAN C-ORGANIK PADA TANAH ULTISOL YANG DIBERI BERBAGAI JENIS BAHAN ORGANIK UNTUK PERTUMBUHAN TANAMAN SAWI - Mujizat, Yuyun; Namriah, Namriah; Leomo, Sitti; Darwis, Darwis; Alam, Syamsu; Resman, Resman (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Ultisol is a potential acid mineral soil for the development of agricultural crops with an area of 45.8 million hectares, but has problems of soil acidity, low content of C-Organic, nitrogen, phosphate and potassium, but this can be overcome by applying fertilizers. This study aims to determine the effect of various types of organic matter on C-Organic and the growth of mustard greens. This research was conducted on Field II of the Faculty of Agriculture, and sample analysis was carried out at UPT. Halu Oleo University Integrated Laboratory.The study used a randomized block design (RBD) consisting of 9 treatments, namely TB = without organic matter, SI = cow manure 75 g polybag-1, SII = cow manure 150 g polybag-1, AI = chicken manure 75 g polybag -1, AII = chicken manure 150 g polybag-1 , KI = goat manure 75 g polybag-1 , KII = goat manure 150 g polybag-1 , HI = compost vegetation komba-komba 75 g polybag-1 , HII = komba-komba vegetation compost 150 g polybag-1.The results showed that the provision of various types of organic matter was 0.62%. As for the results after administration of various types of organic matter with various concentrations continued to decrease successively in the treatment TB, SI, SII, AI, AII, KI, KII, HI, namely 0.26%, 0.28%, 0, 32%, 0.34%, 0.40%, 0.52%, 0.54%, 0.60%, and after that there was an increase in the HII treatment, 0.78%, with a dose of 150 grams. Application of cow manure, chicken coop, goat coop, and komba-komba vegetation compost had an effect on the height of the mustard plants. Keywords : C-Organic, Mustard Plant, Ultisol.